Hypothetical Learning Trajectory on Trigonometric Equations Material - Dita Oktavihari; Gilang Primajati; M. Gunawan Supiarmo (Tinta Emas Institute, 2025)
Difficulties in solving trigonometric equations are not only technical but also occur due to the lack of conceptual understanding possessed by students. This study aims to develop a hypothetical learning trajectory on trigonometric equation material at the upper secondary level that can help students in building conceptual understanding in solving trigonometric equation problems. The research design used is a didactic design with a qualitative research type. This research was conducted at Sekolah Menengah Atas Negeri (SMAN) 5 MATARAM with research subjects of grade XI students. Data collection techniques used were tests, interviews, and document studies. The results obtained were that students did not understand the prerequisite material, did not understand the key things in the problem-solving process, limited context, and teacher difficulties in explaining how to make mathematical models related to contextual problems. Therefore, the researcher designed a Hypothetical learning trajectory to minimize the learning obstacles that arise.